A Western Philosopher’s Thoughts About Islam - Çaksen, Hüseyin (International Journal of Human and Health Sciences (IJHHS), 2025)
Abstract not available International Journal of Human and Health Sciences Vol. 09 No. 01 Jan’25 Page: 22-25